Pengaruh Kualitas Pelayanan Perbankan Syariah Terhadap Kepuasan Nasabah(Studi Pada KB Bank Syariah) - Nadia Dwi Irmadiani (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
The research aims to, Analyze whether the variable partial effect of service quality on customer satisfaction on Islamic Banking at KB Bank Syariah, Determine and analyze whether the variable service quality simultaneously influence on customer satisfaction on islamic Banking at KB Bank Syariah, Knowing which variables amorrg the service variable most dominant influence on customer satisfaction on Islamic Banking at KB Bank Syariah. Analysis of the data in this study using multiple linear regression test and subsequently used the F-test, T and dominant to see the effect of each. The research results indicate that the value of F-test (3,722) > F table (2,437) this indicates that variable Tangibles, Reliability, Responsiveness, Assurance, and Empathy simultaneously (together) effect on customer satisfaction. While the partial test for Tagibles variable (X1) where t test (1,232)> t table (2,577) this indicated that Tangibles no effect on customer satisfaction. For Reliability (X2), t test (3,428) > t table (2,571), that affect the reliability of customer satisfaction. For variable Responsiveness (X3), t test (-0.390) > t table (2,571) Responsiveness no effect on customer satisfaction. To Guarantee (X4), t test (0,549) > t table (2,571), variable warranty does not affect the customer satisfaction. For variable Empathy (X5) regression coefficient of -0,103, the t test (- 0,664 > t table (2,571) and a variable Empathy has no effect on customer satisfaction While the dominant variable in the quality of services that affect customer satisfaction on Islamic banking at KB Bank Syariah is variable Assurance (x4) with a contribution of 51%.